ENVIRONMENTAL FISCAL EFFORT: SPATIAL CONVERGENCE WITHIN ECONOMIC POLICY ON TAXATION - Elena Villar Rubio; Jose Manuel Quesada Rubio; Valentín Molina Moreno (Revista de Economía Mundial, 2017)
Environmental fiscal effort, when compared with environmental fiscal pressure, represents a far more precise parameter when measuring a country’s environmental sacrifice given that it introduces GDP per capita as an analysis variable. This paper focuses on the analysis of convergence in environmental fiscal effort amongst the EU-15 Member States between 1987 and 2008, employing, to this end, the techniques of sigma, beta and gamma convergence. On a complementary level, a spatial autocorrelation study is carried out in order determine whether or not the geographical proximity of countries has any bearing on similar fiscal effort.